Adaptive Parameter Identification Based on Morlet Wavelet and Application in Gearbox Fault Feature Detection. (24th October 2010) - Wang Wang, Shibin Shibin; Zhu Zhu, Z. K. Z. K.; He He, Yingping Yingping; Huang Huang, Weiguo Weiguo
Abstract : Localized defects in rotating mechanical parts tend to result in impulse response in vibration signal, which contain important information about system dynamics being analyzed. Thus, parameter identification of impulse response provides a potential approach for localized fault diagnosis. A method combining the Morlet wavelet and correlation filtering, named Cyclic Morlet Wavelet Correlation Filtering (CMWCF), is proposed for identifying both parameters of impulse response and the cyclic period between adjacent impulses. Simulation study concerning cyclic impulse response signal with different SNR shows that CMWCF is effective in identifying the impulse response parameters and the cyclic period. Applications in parameter identification of gearbox vibration signal for localized fault diagnosis show that CMWCF is effective in identifying the parameters and thus provides a feature detection method for gearbox fault diagnosis.